A STUDY OF DOMINANT COMMUNICATION STYLES AMONG VARIOUS ETHNIC GROUPS IN PT FREEPORT INDONESIA: CHALLENGES AND MANAGEMENT IMPLEMENTATION - Wijaya, Ramdhani Kresna; Pratama, Andika Putra (Journal of Business and Management, 2018)
Abstract.Â Diverse workforce is an increasingly important phenomenon that needs better understanding. Numerous multinational companies that operates in several places in the world hire employees that comes from various part of the world, and one of them is PT Freeport Indonesia. As a multinational company, PT Freeport Indonesia hires Indonesian employees that come from various ethnic group in Indonesia, thus making PT Freeport Indonesia a company which ethnically diverse. This is also applicable in the Facilities and Town Management department â€“ Highland division, one of the departments in PT Freeport Indonesia. Their employee comes from various ethnic backgrounds, thus potentially carry different values and behaviors with them. This research aims to analyze one form of diversity, namely communication styles involving various ethnic groups in the company using a quantitative method (i.e. survey) The outcome of this research is an analysis of dominant communication styles of various ethnic groups, categorized into several groups, and several suggestions on how to manage diversity based on ethnic groups for the Facilities and Town Management department PT Freeport Indonesia. The study found some significant differences in communication style from several group, although only a few were found. Even so, this suggests that even if it is subtle the potential conflicts may appear. Although there are many similarities among groups in each communication style, it does not imply that conflict may not appear. That is why better understanding from each member of the department is essential to minimizes conflict and increase work harmony.Keywords: communication style, cross cultural communication, diversity, ethnic diversity